Proceedings of the Proceedings of the 1st EAI International Conference on Medical and Health Research, ICoMHER November 13-14th 2019
DOI: 10.4108/eai.13-11-2018.2283632
|View full text |Cite
|
Sign up to set email alerts
|

Description of Insulin Resistance and Beta-Cell Pancreas Dysfunction in Prediabetic Patients

Abstract: Prediabetes is the forerunner of diabetes mellitus. Hence it has to be carefully cared for. Main conditions causing this are insulin resistance and beta cell dysfunction. Insulin resistance can be assessed by using several methods, one of which is performed by assessing the value of HOMA-IR. Beta cell function can be determined by assessing HOMA-B. In this research we aim to obtain the description of insulin resistance and beta cell pancreas dysfunction on prediabetic patients, using the analytic observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Progressive, Endurance Training). Beberapa olahraga yang disarankan antara lain jalan atau lari pagi, bersepeda, berenang, dan senam (Decroli, 2019).…”
Section: Pendahuluanunclassified
“…Progressive, Endurance Training). Beberapa olahraga yang disarankan antara lain jalan atau lari pagi, bersepeda, berenang, dan senam (Decroli, 2019).…”
Section: Pendahuluanunclassified
“…The International Diabetes Federation in 2019 reported that the prevalence of pre-diabetes was 373.9 million or 7.5% of the adult population aged 20-79 years worldwide. In Indonesia, there was 29.1 million population with prediabetes in 2019 [1], [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…HOMA-IR can describe insulin resistance. Decroli et al stated that increased insulin secretion compensates for increased HOMA-IR by beta-cell pancreas in pre-diabetic patients [4], [5], [6], [7]. Various studies have proven that in pre-diabetic patients, a prothrombotic state has taken place, which will cause micro-and macro-vascular complications [8], [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%